Digital Transformation in Small- and Medium-Sized Textile Enterprises (SMTEs) in Lagos, Nigeria: Assessing the Adoption of E-Commerce and Enterprise Resource Planning (ERP) for Operational Efficiency and Financial Performance - Aduaye-Odiete, Patrick Onochie (Digital Repository of Theses - SSBM Geneva, 2025)
In the contemporary business landscape, digital transformation has emerged as a critical factor, particularly for small and medium-sized textile enterprises (SMTEs) as they endeavor to harness the potential of digital technologies (e-commerce, ERP systems). Using the theories of Technology-Organization-Environment (TOE) and Resource-Based-View (RBV) as a framework, this study set out to investigate how widespread the use of digital technology is among small and medium-sized enterprises (SMEs) in Lagos, Nigeria, and how this affects their operational efficiencies and financial performance. The researchers used a mixed-methods approach for the study combining both quantitative and qualitative approaches to acquire a comprehensive dataset from SMTEs situated in Lagos, the most extensive City in terms of both size and population in Nigeria. The target population comprised 600 SMTEs in Lagos, out of which 400 responses were received. The SPSS program was used to examine the collected data. Findings reveal that the adoption rate of digital technologies among SMTEs in Lagos is relatively low at 46.5%. However, enterprises leveraging e-commerce and ERP systems reported significant improvements in sales, market size, and customer satisfaction. Correlation and regression analyses confirmed a positive relationship between digital technology adoption and sales growth, while chi-square tests highlighted the role of e-commerce in market expansion. The Improved customer engagement and satisfaction were attributed to progress customer relationship management and online shopping experiences facilitated by these technologies. Additionally, key performance indicators such as “Gross profit margin, return on sales (ROS), and Return on assets (ROA)” showed a positive correlation with the adoption of digital technologies, underscoring their role in driving sustainable financial performance. A new corpus of literature will be added to by the study's findings on digital transformation, as positive social change by driving digital transformation by the SMTEs through the implementation of digital technologies and its subsequent impact on their operational efficiencies and financial performance in Lagos and generally within the SMTEs sector in Nigeria. In addition, the research outcomes are anticipated to make significant contributions to informing policymakers and industry stakeholders on some of the potential benefits and challenges associated with the acceptance and application of digital technologies. Keywords: Digital Transformation, Small and Medium-Sized Textile Enterprises (SMTSs), Digital Technologies, Adoption, Implementation, Sustainable Financial Growth, Mixed-Methods Research, Nigeria.